2021
DOI: 10.1242/jcs.257006
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular and intracellular cilia orientation is coordinated by CELSR1 and CAMSAP3 in oviduct multi-ciliated cells

Abstract: The molecular mechanisms by which cilia orientation is coordinated within and between multiciliated cells (MCCs) are not fully understood. In the mouse oviduct, MCCs exhibit a characteristic BB orientation and microtubule gradient along the tissue axis. The intracellular polarities were moderately maintained in the cells lacking CELSR1, a planar cell polarity (PCP) factor involved in tissue polarity regulation, although the intercellular coordination of the polarities was disrupted. Whereas CAMSAP3, a microtub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…A recent study showed that CAMSAP3 is expressed in nasal multiciliated cells, and its absence causes defects in ciliary motion and polarity (Robinson et al, 2020). Similar observations were also reported using oviduct cells (Usami et al, 2021). However, how CAMSAP3 sustains the structure and function of multicilia remains to be investigated.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…A recent study showed that CAMSAP3 is expressed in nasal multiciliated cells, and its absence causes defects in ciliary motion and polarity (Robinson et al, 2020). Similar observations were also reported using oviduct cells (Usami et al, 2021). However, how CAMSAP3 sustains the structure and function of multicilia remains to be investigated.…”
Section: Introductionsupporting
confidence: 54%
“…To begin investigating how CAMSAP3 contributes to microtubule assembly in axonemes, we observed its distribution in airway epithelial cells of adult trachea by immunofluorescence (IF) microscopy, using samples fixed with paraformaldehyde (PFA). The results showed that CAMSAP3 was concentrated around the apical plasma membranes (Figure 3A), as assessed by co-immunostaining for EZRIN, which is known to associate with the apical membranes or microvilli (Berryman et al, 1993), as observed in other epithelial cells (Toya et al, 2016;Robinson et al, 2020;Kimura et al, 2021;Usami et al, 2021). This position of CAMSAP3 corresponded to the proximal edge of strong -tubulin IF signals that should represent ciliary microtubules (Figure 3B).…”
Section: Concentration Of Camsap3 Around the Proximal Ends Of Ciliamentioning
confidence: 63%
“…To begin investigating how CAMSAP3 contributes to microtubule assembly in axonemes, we observed its distribution in airway epithelial cells of adult trachea by immunofluorescence (IF) microscopy, using samples fixed with paraformaldehyde (PFA). The results showed that CAMSAP3 was concentrated around the apical plasma membranes (Figure 3A), as assessed by co-immunostaining for EZRIN, which is known to associate with the apical membranes or microvilli (Berryman et al, 1993), as observed in other epithelial cells (Toya et al, 2016;Robinson et al, 2020;Kimura et al, 2021;Usami et al, 2021). This position of CAMSAP3 corresponded to the proximal edge of strong a-tubulin IF signals that should represent ciliary microtubules (Figure 3B).…”
Section: Concentration Of Camsap3 Around the Proximal Ends Of Ciliamentioning
confidence: 63%
“…It has been reported that the Centriolin staining pattern is a good marker to categorize MCCs during differentiation. MCCs can be found in stage I with a pair of centrioles, stage II/III with many centrioles aggregated and migrating, and stage IV/V with many centrioles homogeneously distributed at the apical membrane ( Usami et al, 2021 ). We found that Jam3 KD cells had a significant delay in MCC maturation since only 10% of MCCs are in stage IV/V in ALI 5 compared to 70% in control cells ( Figures 4N–P ).…”
Section: Resultsmentioning
confidence: 99%